2023
DOI: 10.3389/fpubh.2023.1142461
|View full text |Cite
|
Sign up to set email alerts
|

A propensity score matching study: The prevalence of mental health problems among pregnant women at first antenatal care increased in Chongqing during the first wave of the COVID-19 pandemic

Abstract: BackgroundThe 2019 coronavirus disease (COVID-19) pandemic increased the risks of mental health challenges, especially anxiety and depression. However, the impact of COVID-19 on mental health during pregnancy has not been fully established. Therefore, we investigated the impact of the COVID-19 pandemic on maternal mental health.MethodsTwo cohorts of pregnant women at their first antenatal care in the First Affiliated Hospital of Chongqing Medical University were enrolled in this study. One cohort was enrolled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Online help-seeking behaviors have also been proved to be related to negative emotions (30), which is a way for people to seek stress relief. In the face of public health emergencies such as earthquakes, people are not immune to showing fear and anxiety, while in the case of COVID-19 pandemic, a number of studies have demonstrated that people's psychological stress increases during this time (31)(32)(33)(34). When confronted with long and extensive closures such as Wuhan and Shanghai outbreaks, the reasonable scheduling of resources has also become a difficult problem faced by the administrators.…”
Section: Introductionmentioning
confidence: 99%
“…Online help-seeking behaviors have also been proved to be related to negative emotions (30), which is a way for people to seek stress relief. In the face of public health emergencies such as earthquakes, people are not immune to showing fear and anxiety, while in the case of COVID-19 pandemic, a number of studies have demonstrated that people's psychological stress increases during this time (31)(32)(33)(34). When confronted with long and extensive closures such as Wuhan and Shanghai outbreaks, the reasonable scheduling of resources has also become a difficult problem faced by the administrators.…”
Section: Introductionmentioning
confidence: 99%